New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae) - Jukka Salmela; Anna Suuronen; Kari M. Kaunisto (Pensoft Publishers, 2022)
Abstract
Background
The genus Boletina is a species rich group of fungus gnats. Members of the genus are mainly known from temperate, boreal and arctic biomes. Phylogeny of the genus is still poorly resolved, dozens of species are insufficiently described and undescribed species are often discovered, especially from samples taken from the boreal zone.
New information
Four new species are described. Boletina valteri Salmela sp.n. (Finland), Boletina kullervoi Salmela sp.n. (Finland), B. hyperborea Salmela sp.n. (Finland, Norway, Sweden, Canada) and B. nuortti Salmela sp.n. (Finland). Boletina arctica Holmgren is redescribed and reported for the first time from the Canadian high arctic zone. Boletina borealis Zetterstedt and B. birulai Lundström are reported for the first time from Canada. Boletina subnitidula Sasakawa (syn. n.) is proposed as a junior synonym of B. pallidula Edwards.